Genomic and proteomic identification of Aeromonas isolates from diverse sources: comparative performance of WGS and MALDI-TOF MS in species-level resolution - Vieira, Thais; Costa, Gisele Lozano; Yamada, Amanda Yaeko; Bertani, Amanda Maria de Jesus; Medeiros, Marta Ines Cazentini; Moreno, Luisa Zanolli; Moreno, Andrea Micke; Costa, Christiane Asturiano Ristori; Campos, Karoline Rodrigues; Benedito, Marlon; Sacchi, Claudio Tavares; Camargo, Carlos Henrique; et al. (Frontiers in Bacteriology, 2025)
The accurate identification and characterization of Aeromonas species are essential to understand their ecological roles and potential health impacts. This study analyzed 90 Aeromonas isolates from various sources using whole genome sequencing (WGS) and matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS). Species identification by WGS, based on Average Nucleotide Identity (ANI ≥96%), revealed inconsistencies in 12.2% of MALDI-TOF MS results, for species not represented in its database. Phylogenetic analyses using single nucleotide polymorphism (SNP) data were concordant in resolving species-level clusters and revealing intra-species diversity. This study reinforces the value of WGS and complementary genomic approaches as reliable tools for Aeromonas species identification, population structure analysis, and integrated One Health surveillance. The integration of genomic tools into routine diagnostics may enhance the capacity of laboratories, particularly in low and middle income countries to monitor emerging resistance and better understand the evolutionary and epidemiological dynamics of Aeromonas in clinical and environmental settings.